A census of 4-valent half-arc-transitive graphs and arc-transitive digraphs of valence two - Potočnik, Primož (Ars mathematica contemporanea, 2015)
A complete list of all connected arc-transitive asymmetric digraphs of in-valence and out-valence 2 on up to 1000 vertices is presented. As a byproduct, a complete list of all connected 4-valent graphs admitting a half-arc-transitive group of automorphisms on up to 1000 vertices is obtained. Several graph-theoretical properties of the elements of our census are calculated and discussed.
Keywords: arc-transitive; digraf; digraphs; edge-transitive; graf; graphs; half arc-transitive; ločna tranzitivnost; pol-ločna tranzitivnost; povezavna tranzitivnost; točkovna tranzitivnost; vertex-transitive